SAT0186 The Homeoprotein Engrailed-1 Regulates Canonical TGF-β Signaling via Fibroblast Differentiation and Tissue Fibrosis. (15th July 2016) - Mallano, T.; Palumbo-Zerr, K.; Beyer, C.; Dees, C.; Huang, J.; Wohlfahrt, T.; Distler, O.; Schett, G.; Distler, J.H.
Abstract : Background: Systemic sclerosis (SSc) is a chronic fibrotic connective disease of unknown etiology that affects the skin and internal organs. Transforming growth factor-β (TGFβ) has been characterized as a key-mediator of fibroblast activation in SSc. However, the intracellular signaling cascades that control TGFβ signaling and the TGFβ-induced activation of fibroblasts are still incompletely understood. Homeobox containing transcription factor, Engrailed-1 plays a key role in embryonic development and has also been linked to disease, including cancer. EN-1 is induced by proinflammary cytokines and oxidative stress which play an important role in Systemic Sclerosis (SSc). Objectives: The aim of this study was to determine the role of the embryonic homeoprotein EN-1 in fibroblast activation and tissue fibrosis in systemic sclerosis (SSc). Methods: The expression of EN-1 in skin tissue and in human dermal fibroblasts was determined by real-time PCR, Western blot and immunofluorescence. Knock-down and overexpression strategies were used to evaluate the effect of EN-1 on fibroblast activation. The outcome of mice with fibroblast-specific knockout of EN-1 (EN1 fibKO) was evaluated in bleomycin-induced skin fibrosis; fibrosis induced by overexpression of a constitutively active TGF-β receptor I (TBRIact) and in the Tsk model which resembled the later stages of SSc. Co-IP and CAGA Reporter assay were performed to study the physical and functional interaction between EN-1 and Smad3. Results: A five-fold increased expression of EN-1 was detected in the upper layer of the dermis of SSc patients on fibroblasts double stained for EN-1 and anti-prolyl-4-hydroxylase. EN-1 expression was induced by TGF-β in cultured fibroblasts and treatment with the TBR inhibitor SD-208 prevented the induction of EN-1 by two-fold decrease in experimental fibrosis. Fibroblasts lacking EN-1 were less sensitive to the pro-fibrotic effects of TGF-β with impaired induction of target genes mRNA and protein. Additionally, overexpression of EN-1 enhanced the profibrotic effect of TGF-β with myofibroblast differentiation and increased collagene release as well as mRNA and protein levels of target genes. Function studies demonstrated that EN-1 interacts with Smad3 to regulate the pro-fibrotic effects of TGF-β. Co-IP demonstrated that TGF-β induces binding of EN-1 to Smad3. Reporter study and analyses of the expression of classical Smad target genes such as PAI-1 demonstrated that the binding of EN-1 to Smad3 stimulates the transcriptional activity of Smad3. In the model of bleomycin-induced fibrosis dermal thickening, hydroxyproline content and myofibroblast counts were significantly decreased in EN1 fibKO mice as compared to wildtype littermates. EN1 fibKO also protected from TBRIact-induced fibrosis and ameliorated fibrosis in the Tsk1 model. Conclusions: We demonstrate for the first time a role of EN-1 in fibroblast activation and tissue fibrosis. Deficiency in EN-1 reduced the stimulatory effect of TGF-β on fibroblasts by interfering with canonical Smad and protected from experimental fibrosis in different mouse models. Considering the potent anti-fibrotic effects observed in this study, EN-1 might be a candidate for molecular targeted therapies of SSc. Disclosure of Interest: None declared